ANALISIS SPASIOTEMPORAL LAND SURFACE TEMPERATURE DAN AIR SURFACE TEMPERATURE MENGGUNAKAN LANDSAT 8 TAHUN 2018, 2019, DAN 2025 DI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS INDONESIA - wardahni, Farah Septia (JURNAL GEOGRAFI, 2025)
Urban Heat Island (UHI) phenomenon causes higher urban temperatures than its surrounding areas. UHI comprises both Land surface temperature (LST) and Air Surface Temperature (AST) that are interrelated. LST is often linked to surface properties of landcover types with its influencing parameters, including surface material, vegetation, and soil moisture. Whereas AST is determined based on LST-based modeling, with field based measurement. Research analysis was conducted in Universitas Indonesia (UI), and the Faculty of Health Sciences (FKM), characterized by its unique landcovers, including dispersed vegetation, water bodies, and built-up areas, using Landsat 8 imagery.The results show that LST 2018, 2019, 2015 ranged 19,20 - 39,68 °C, with low temperatures in vegetation and water bodies, and high temperatures in asphalt and buildings. 2018 and 2019 AST using various linear models ranged 16,14 - 35,74 °C, and 2025 AST using the model best represents the actual temperature ranging 29,50 - 34,76 °C for UI and 31,44 - 32,47 °C for FKM. Field measurement conducted at building, vegetation, and impervious areas resulted in 31,80 - 35,07 °C temperature range. M-AST model shows 0,9988 × LST + 4,3082 regression produces results most closely matched to the field measurements. Keywords :UHI, LST, AST, Landsat 8, Universitas Indonesia